Penerapan Metode Qira’ah Menggunakan Kitab Al-Arabiyyah Baina Yadaik di Kelas 2a Salafiyah Wustha Islamic Centre Bin Baz Yogyakarta - Aminudin Jeri Satria; Saiful Anam; Ghossan Althof (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The development of methods in Arabic language learning in Islamic educational institutions has undergone various innovations, one of which is through the implementation of the qira'ah method using the Al-Arabiyyah Baina Yadaik textbook. This research aims to examine how the qira'ah method is implemented using the Al-Arabiyyah Baina Yadaik textbook for students in class 2A at Salafiyah Wustha Islamic Centre Bin Baz Yogyakarta. The qira'ah method, which emphasizes the ability to read and understand Arabic texts, becomes a strategic approach in comprehensively mastering the Arabic language. The Al-Arabiyyah Baina Yadaik textbook, as a systematic and integrated learning reference, is often chosen to develop students' language skills. Through the structured and contextual approach offered by this textbook, it is highly expected that students' ability to read and understand Arabic texts can increase significantly. This research uses a qualitative descriptive approach with observation, interview, and documentation techniques. The research findings show that the implementation of the qira'ah method using the Al-Arabiyyah Baina Yadaik textbook has successfully improved the reading ability and understanding of Arabic texts among the students in class 2A. In conclusion, the selection of appropriate methods and teaching materials plays an important role in improving the effectiveness of Arabic language learning, particularly in developing reading and text comprehension skills in pesantren-based educational institutions such as Islamic Centre Bin Baz Yogyakarta.